Vitamin A metabolism in benign and malignant melanocytic skin cells: importance of lecithin/retinol acyltransferase and RPE65 - Amann, Philipp M.; Luo, Chonglin; Freudenberger, Muriel; Eichmüller, Stefan B.; Bazhin, Alexandr V. (Journal of cellular physiology, 2012)
Disturbance in vitamin A metabolism seems to be an important attribute of cancer cells. Retinoids, particularly retinoic acid, have critical regulatory functions and appear to modulate tumor development and progression. The key step of vitamin A metabolism is the esterification of all-trans retinol, catalyzed by lecithin/retinol acyltransferase (LRAT). In this work, we show that malignant melanoma cells are able to esterify all-trans retinol and subsequently isomerize all-trans retinyl esters (RE) into 11-cis retinol, whereas their benign counterparts-melanocytes are not able to catalyze these reactions. Besides, melanoma cell lines express lecithin/retinol acyltranseferase both at the mRNA and protein levels. In contrast, melanocytes do not express this enzyme at the protein level, but mRNA of lecithin/retinol acyltransefrase could still be present at mRNA level. RPE65 is expressed in both melanocytic counterparts, and could be involved in the subsequent isomerization of RE produced by lecithin/retinol acyltransefrase to 11-cis retinol. Cellular retinol-binding protein 2 does not appear to be involved in the regulation of all-trans retinol esterification in these cells. Expression of LRAT and RPE65 can be modulated by retinoids. We propose that the post-transcriptional regulation of lecithin/retinol acyltransefrase could be involved in the differential expression of this enzyme. Besides, activities of LRAT and RPE65 may be important for removal of all-trans retinal which is the substrate for retinoic acid production in skin cells. Consequently, the decreasing cellular amount of retinoic acid and its precursor molecules could result in a change of gene regulation.